Determinants of Financial Inclusion: Evidence from the Gulf Cooperation Council Countries - Alqudaib, Nada; Sallam, Mohamed A. M. (Journal of Posthumanism, 2025)
This research paper provides an in-depth analysis of the primary determinants of financial inclusion in Gulf Cooperation Council countries from 2010 to 2023. Using a sound methodological framework, the study first developed a comprehensive Financial Inclusion Index for each member state, based on the multidimensional approach proposed by Sarma (2008). Furthermore, an ARDL model was estimated using the Pooled Mean Group estimator to analyze the short- and long-run relationships between the Financial Inclusion Index and its potential determinants, while accounting for cross-sectional dependence across countries. The results show significant and continuous improvements in the financial inclusion indicators across all GCC countries, with indicators now in the high financial inclusion categories. Three key long-term drivers were identified through the econometric analysis: the Human Development Index, internet penetration, and the dependency ratio. Interestingly, both the Human Development Index and internet use had a statistically significant positive impact, highlighting the fundamental roles of human capital and digital infrastructure in development. A positive nexus between the dependency ratio and financial inclusion was also observed, a finding that runs counter to conventional literature but can be explained by the region’s high income levels and comprehensive social welfare systems, which route support through formal banking channels. The error-correction model confirmed a stable long-term equilibrium, with 32.7% of short-term deviations corrected each year. The policy recommendations presented in this paper conclude by calling for the adoption of integrated strategies that link financial inclusion with human development and digital transformation agendas, while enhancing regional cooperation to accelerate progress toward the desired outcomes